2014
DOI: 10.1007/s11764-014-0343-9
|View full text |Cite
|
Sign up to set email alerts
|

Quality of cancer follow-up care: a focus on Latina breast cancer survivors

Abstract: Introduction Receiving quality cancer follow-up care influences survivorship outcomes. Among Latinas, breast cancer is the number one cause of cancer death; yet Latinas do not receive adequate follow-up care. This study examined quality of cancer follow-up care among Latina breast cancer survivors (BCS) and whether it differs by participant language and healthcare system variables (provider specialty, and medical setting). Methods Two hundred thirty-two (95 English-speaking Latina and 137 Spanish-speaking) L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…The 3‐item measure includes items on patient‐provider communication and rapport (eg, “Doctors and health professionals answer all my questions”) on a 5‐point Likert scale (1―strongly disagree to 5―strongly agree) with higher scores indicating greater perceived satisfaction with communication. The measure demonstrated good reliability in previous studies and for this entire study sample ( α = .63) and for African‐American ( α = .74) and Latina ( α = .58) YBCS.…”
Section: Methodssupporting
confidence: 52%
“…The 3‐item measure includes items on patient‐provider communication and rapport (eg, “Doctors and health professionals answer all my questions”) on a 5‐point Likert scale (1―strongly disagree to 5―strongly agree) with higher scores indicating greater perceived satisfaction with communication. The measure demonstrated good reliability in previous studies and for this entire study sample ( α = .63) and for African‐American ( α = .74) and Latina ( α = .58) YBCS.…”
Section: Methodssupporting
confidence: 52%
“…Satisfaction with survivorship information also is a strong predictor of vitality and mental health . In the same vein, evidence suggests that patient satisfaction is a strong correlate of survival as well as quality of survivorship, and language, literacy, and culture barriers faced by Latinas negatively affect survival as well as quality of survivorship …”
Section: Introductionmentioning
confidence: 99%
“…4 In the same vein, evidence suggests that patient satisfaction is a strong correlate of survival as well as quality of survivorship, and language, literacy, and culture barriers faced by Latinas negatively affect survival as well as quality of survivorship. 15,16 The current study analyzed data from the baseline questionnaire of a randomized controlled trial of survivorship care plans in low-income survivors of BC 17 to assess gaps in knowledge, survivorship preparedness, and satisfaction with information received between Latinas and non-Latina patients.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have shown Spanish-speaking Latina breast cancer survivors receive less follow-up than both English-speaking Latina and white breast cancer survivors. [ 11 12 ] It is apparent through the study of bladder cancer and other malignancies that significant disparity exists in treatment and surveillance between people of different socioeconomic status. As a result, minorities that fall within a lower socioeconomic group may suffer decreased follow-up possibly contributing to worse outcomes.…”
Section: Discussionmentioning
confidence: 99%